PERSONALITY-ORIENTED APPROACH TO THE ORGANIZATION OF STUDENTS’ SELF-GUIDED WORK - Olena L. Pinska (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2019)
The problem of organizing self-guided work of students in the conditions of personality-oriented education is a topical and key one in the strategic directions of building a qualitatively new system of training pedagogical personnel. Self-guided work requires from students an internal readiness for intense mental activity, aimed at the formation of independence as a personal trait and the development of creative thinking. The individual nature of self-guided work for its effective organization based on a personalityoriented approach involves revealing and disclosing the subjective experience of each student and its coordination with the peculiarities of the educational opportunities of the conditionally allocated three dynamic multi-level typological groups of students (students with high, medium, and low level of educational opportunities), which allows to make a level differentiation of tasks for independent cognitive activity. Tasks for students of the first group should be creative and research ones. Students of the second group are offered search tasks, students of the third group are offered tasks of the reproductive nature. Taking into account their own educational opportunities, each student must learn at the reproductive level the compulsory minimum content of subjects allocated for self-guided studies, which are necessary to ensure professional training. Personality-oriented approach involves an organization of self-guided work, according to which students have the right to implement it at various planned levels, which creates a possibility for the transition from one to another group of a higher level for everyone. Voluntary ascent from the compulsory to higher level can actually provide a student with a permanent stay in the zone of “proximal development” – training at an individual maximum feasibility level. When performing self-guided work, individual cognitive activity prevails, during which the successes and failures of one student do not directly affect the successes and failures of another one; therefore, it is advisable to practice uniting students of different dynamic groups into one “mixed” group, creating conditions for joint search, choosing the best options for solving educational problems of different levels of complexity. The collective implementation of tasks at various levels contributes to increasing the educational opportunities for each student and the transition to a higher-level dynamic group. Organizations of self-guided work on the basis of a personality-oriented approach can create suitable regime for students’ individual cognitive activities with different educational opportunities, which contributes to self-development and self-realization of the future teachers’ personality.